2012
DOI: 10.1371/journal.pone.0032720
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of Selection in the Genomes of Commercial and Non-Commercial Chicken Breeds

Abstract: Identifying genomics regions that are affected by selection is important to understand the domestication and selection history of the domesticated chicken, as well as understanding molecular pathways underlying phenotypic traits and breeding goals. While whole-genome approaches, either high-density SNP chips or massively parallel sequencing, have been successfully applied to identify evidence for selective sweeps in chicken, it has been difficult to distinguish patterns of selection and stochastic and breed sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
85
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(103 citation statements)
references
References 52 publications
14
85
0
Order By: Relevance
“…The availability of genomic data that has been generated using genome-wide single nucleotide polymorphism (SNP) analyses and the comparison of genomic patterns of SNP variation between divergent breeds has successfully identified putative genomic regions and genes associated with differences in selection pressure in various livestock species including sheep (Kijas et al, 2012;Lv et al, 2014), Yak (Qiu et al, 2012), cattle (Xu et al, 2015) and chicken (Elferink et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The availability of genomic data that has been generated using genome-wide single nucleotide polymorphism (SNP) analyses and the comparison of genomic patterns of SNP variation between divergent breeds has successfully identified putative genomic regions and genes associated with differences in selection pressure in various livestock species including sheep (Kijas et al, 2012;Lv et al, 2014), Yak (Qiu et al, 2012), cattle (Xu et al, 2015) and chicken (Elferink et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…When genome-wide marker panels are used for selection, it is possible to use these markers to investigate the dynamics of allelic diversity across the genome. Most methods developed for assessing the allelic diversity through genomic analysis are based on calculating population genetics statistics such as allele frequencies (either directly or indirectly) (Elferink et al, 2012) and linkage disequilibrium (LD) (Ennis, 2007). Previous studies have shown that frequencies of the favorable alleles, as well as alleles in neighboring regions, increase over time when a favorable mutation occurs in a population under selection (Smith and Haigh, 1974;Barton, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, population genomics studies, which search for genetic signatures of selection in the genome (Akey, 2009), have been conducted using high density SNPs genotyping and whole genome sequencing techniques in the livestock genome (e.g., Rubin et al, 2010;Elferink et al, 2012;Fan et al, 2013;Qanbari et al, 2015). This population genomics approach has allowed gene-level resolution mapping of loci that have been positively selected for, without any phenotypic information (Qanbari et al, 2014).…”
Section: Discussionmentioning
confidence: 99%